Can anyone solve this recurrance relation ASAP, em desparate for solutions...

1. An = A^(3) n - 1 A^(2) n - 2 if A0 = 0 and A1 = 2.

Printable View

- May 31st 2008, 06:51 PMJay deeSolving recurrance relation using any technique
Can anyone solve this recurrance relation ASAP, em desparate for solutions...

1. An = A^(3) n - 1 A^(2) n - 2 if A0 = 0 and A1 = 2. - Jun 1st 2008, 04:11 AMtopsquark
Something is off here. Taking what you typed literally this reads

$\displaystyle A_n = (A_n)^3 - (A_n)^2 - 2$

which is not a recurrence.

Did you mean $\displaystyle A_n = (A_{n - 1})^3 \cdot (A_{n - 2})^2$?

The trouble is there that with $\displaystyle A_0 = 0$ the entire sequence is 0.

-Dan